The Insulin Response to Oral Glucose in GIP and GLP-1 Receptor Knockout Mice: Review of the Literature and Stepwise Glucose Dose Response Studies in Female Mice - Ahrén, Bo; Yamada, Yuichiro; Seino, Yutaka (Frontiers in Endocrinology, 2021)
A key factor for the insulin response to oral glucose is the pro-glucagon derived incretin hormone glucagon-like peptide-1 (GLP-1), together with the companion incretin hormone, glucose-dependent insulinotropic polypeptide (GIP). Studies in GIP and GLP-1 receptor knockout (KO) mice have been undertaken in several studies to examine this role of the incretin hormones. In the present study, we reviewed the literature on glucose and insulin responses to oral glucose in these mice. We found six publications with such studies reporting results of thirteen separate study arms. The results were not straightforward, since glucose intolerance in GIP or GLP-1 receptor KO mice were reported only in eight of the arms, whereas normal glucose tolerance was reported in five arms. A general potential weakness of the published study is that each of them have examine effects of only one single dose of glucose. In a previous study in mice with genetic deletion of both GLP-1 and GIP receptors we showed that these mice have impaired insulin response to oral glucose after large but not small glucose loads, suggesting that the relevance of the incretin hormones may be dependent on the glucose load. To further test this hypothesis, we have now performed a stepwise glucose administration through a gastric tube (from zero to 125mg) in model experiments in anesthetized female wildtype, GLP-1 receptor KO and GIP receptor KO mice. We show that GIP receptor KO mice exhibit glucose intolerance in the presence of impaired insulin response after 100 and 125 mg glucose, but not after lower doses of glucose. In contrast, GLP-1 receptor KO mice have normal glucose tolerance after all glucose loads, in the presence of a compensatory increase in the insulin response. Therefore, based on these results and the literature survey, we suggest that GIP and GLP-1 receptor KO mice retain normal glucose tolerance after oral glucose, except after large glucose loads in GIP receptor KO mice, and we also show an adaptive mechanism in GLP-1 receptor KO mice, which needs to be further examined.